BANTUAN REVIEW DAN REKONSILIASI VAT OUT BULAN JANUARI DAN FEBUARI 2025 DENGAN REVENUE DI MITRA - Kristian, Michelle; Nicodemus Lieputra; Louis Fernando; Samuel Kristian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Monthly VAT reconciliation and training activities related to Output VAT are the focus of this Community Service Program (PKM). This PKM activity represents a critical and periodic process that entities must routinely perform. Monthly VAT reconciliation is closely linked to the annual tax return (SPT) reporting. It involves matching periodic data from the monthly VAT Periodic Return (SPT Masa) with the entity’s Annual VAT Return (SPT Tahunan). Discrepancies in VAT data often arise due to differences in sales and purchase transaction characteristics and timing differences, which can be corrected through adjustments. VAT reconciliation is essential because VAT directly affects the entity’s income balances. This PKM addresses reconciliation challenges related to tax factors, such as VAT subject classification, VAT imposition basis, and timing differences in revenue recognition. The activities include assistance with monthly VAT reconciliation for January and February 2025 and training on Output VAT reconciliation with revenue accounts. This training is crucial as every form of revenue from the delivery of Taxable Goods and Services (BKP/JKP) is subject to VAT and must be accurately recognized in income statements. The methodology used in this PKM consists of preparation, implementation, and evaluation phases. The outcome of this PKM is the successful reconciliation of revenue recognition between the trial balance and the profit and loss statement, ensuring consistency with monthly VAT Periodic Returns. Additionally, the Tarumanagara University Faculty of Economics and Business team developed a training module on Output VAT reconciliation as part of the program’s deliverables. ABSTRAK Kegiatan Pengabdian kepada Masyarakat (PKM) ini berfokus pada pendampingan dan pelatihan terkait rekonsiliasi Pajak Pertambahan Nilai (PPN) keluaran (VAT Out) dengan akun pendapatan (Revenue). Rekonsiliasi PPN secara bulanan merupakan aktivitas penting yang dilakukan secara periodik oleh entitas, karena berhubungan langsung dengan pelaporan SPT Masa dan SPT Tahunan. Ketidaksesuaian antara data PPN dalam SPT Masa dengan SPT Tahunan umumnya disebabkan oleh perbedaan waktu pengakuan pendapatan, karakteristik transaksi, serta aspek perpajakan seperti subjek dan dasar pengenaan PPN. Kegiatan PKM ini mencakup bantuan rekonsiliasi PPN untuk periode Januari dan Februari 2025, serta pelatihan yang menekankan pentingnya kesesuaian antara VAT Out dan akun Revenue. Metode yang digunakan dalam kegiatan ini meliputi tahapan persiapan, pelaksanaan, dan evaluasi. Pada tahap persiapan, tim melakukan analisis awal terhadap dokumen pendukung dan data akuntansi. Tahap pelaksanaan mencakup sesi pelatihan interaktif dan diskusi kasus nyata yang dihadapi mitra. Evaluasi dilakukan untuk menilai efektivitas pelatihan dan hasil rekonsiliasi. Hasil dari kegiatan ini adalah tercapainya kesesuaian saldo pendapatan dalam Trial Balance dan laporan laba rugi dengan pelaporan dalam SPT Masa PPN, serta penyusunan modul pelatihan sebagai luaran kegiatan. Kegiatan ini diinisiasi oleh tim dari FEB Universitas Tarumanagara sebagai upaya mendukung kepatuhan pelaporan pajak yang akurat, transparan, dan berkelanjutan, sekaligus meningkatkan kapasitas mitra dalam pengelolaan pajak yang tepat.